A study on the effect of host plants on Chinese gallnut morphogenesis - Qin Lu; Hang Chen; Jinwen Zhang; Weiwei Wang; Yongzhong Cui; Juan Liu (PLoS ONE, 2023)
Galls are products of the hyperplasia of host plant structures induced by gall-inducing organisms and have been considered as an extended phenotype of the inducers. There is little evidence regarding the effect of host plants on gall morphology. We hypothesised that the morphology and developmental pattern of galls are different because of the different location of their stimulation, even though two kinds of inducers are close relatives. We observed that horned galls and their leaflets of their host plant, Rhus chinensis required a longer rapid growth stage than fusiform galls and Rhus potaninii leaflets. The distribution of trichomes showed positional dependence. Molecular analysis showed that in the fusiform gall, the target genes that regulate the plastochron of leaflets and serration development were hardly expressed, and CUP-SHAPED COTYLEDON-2 may be a key gene that regulates the formation of the horns. In summary, horned and fusiform galls showed a developmental pattern similar to those of their host plant leaflets. We suggest that the inducing site is important in the morphology and development of galls.